Intensitas Penggunaan Produk Impor di Kalangan Mahasiswa UPI Cibiru Angkatan 2022 - Karina Dewi Julianida Firman; Muhammad Fahmi Fauzi; Tin Rustini (FKIP, Universitas Palangka Raya, 2023)
Humans in meeting their needs always require various kinds of goods or supporting products. Every human being must have needs that must be met. The existence of economic activity helps people meet their needs. Economic activity includes the process of production, distribution, and consumption. This means that trade is also included in economic activity. Along with the development of the times, especially in the development of globalization, trade is carried out not only domestically. Trade carried out by several countries is divided into two, namely export and import activities. Export and import activities certainly have a correlation or relationship with the rate of economic development of a country. It is also undeniable that this economic activity can influence people's behavior. The large number of foreign products that enter causes consumptive behavior towards foreign goods. The research will determine the intensity of the use of imported goods among students at the Indonesian University of Education, Cibiru Campus. This research is qualitative research that emphasizes a process without being tested using descriptive data.